Isolation and culture of primary adult skin fibroblasts from the Asian elephant ( Elephas maximus ) - Siengdee, Puntita; Klinhom, Sarisa; Thitaram, Chatchote; Nganvongpanit, Korakot (PeerJ (San Francisco, CA), 2018)
Primary cultures from Asian elephants ( ) allow scientists to obtain representative cells that have conserved most of their original characteristics, function, physiology and biochemistry. This technique has thus gained significant importance as a foundation for further cellular, cell biology and molecular research. Therefore, the aim of this study was to describe conditions for the successful establishment of primary adult fibroblasts from Asian elephant carcasses. Ear tissue sample collection from Asian elephant carcasses and our recommendations are given. We describe here a simple modified protocol for successful isolation and maintenance of primary adult fibroblasts from elephant ear skin. Ear samples from each individual (five 3 × 3 cm pieces) were brought to the laboratory within 3 h after collection, kept in transportation medium at 0-4 °C. The ear tissues were prepared by a combination of 10% collagenase type II digestion procedure together with a simple explant procedure. Primary fibroblasts were cultured at 37 °C in Dulbecco's modified Eagle's medium (DMEM) with 20% fetal calf serum (FCS) in a humidified atmosphere containing 5% CO . After the third passage, fibroblasts were routinely trypsinized with 0.25% trypsin/EDTA and cultured in DMEM with 10% FCS at 37 °C and 5% CO . Traditional cell counting method was used to measure cell viability and growth curve. Long-term storage of cells used freezing medium consisting of 40% FCS (v/v). We explored the most suitable conditions during sample collection (post-mortem storage time and sample storage temperature), which is the most important step in determining primary outgrowth. Our study successfully established and cultured primary adult skin fibroblasts obtained from post-mortem ear skin tissues from six carcasses, with a success rate of around 83.3%. Outgrowth could be seen 4-12 days after explantation, and epithelial-like cells were found after 4-7 days of culture, while fibroblasts appeared at around day 7-10. The fibroblasts had viability and post-freezing recovery rates of around 97.3 ± 4.3% and 95.5 ± 7.3%, respectively, and doubling time was about 25 h (passage 6). To our knowledge, this report is the first to describe primary cell cultures derived from adult Asian elephant skin. Future studies should benefit from the information and useful suggestions herein, which may be used as a standard method for establishing primary skin fibroblast cultures in future experiments.